Assumptions About Behavior and Choice in Response to Public Assistance: A Behavioral Decision Analysis. (October 2014) - Hall, Crystal C.; Galvez, Martha M.; Sederbaum, Isaac M.
Assumptions about decision making and consumer preferences guide programs and products intended to help low-income households achieve healthy outcomes and financial stability. Despite their importance to service design and implementation, these assumptions are rarely stated explicitly, or empirically tested. Some key assumptions may reflect ideas carried over from an earlier era of social-service delivery. Or they may reflect research on decision making by higher income populations that do not hold or have not been tested in a low-income context. This disconnect between assumptions and evidence potentially results in less effective policy design and implementation—at substantial financial and social cost. This piece examines how insights from psychology can help policymakers analyze the core assumptions about behavior that underlie policy outcomes. Three policy areas serve as case studies, to examine some implicit and explicit assumptions about how low-income individuals make decisions under public and nonprofit assistance: banking, nutrition, and housing. Research on preferences and decision making evaluates these foundational assumptions. This perspective provides a unique and under-utilized framework to explain some behavioral puzzles, examine and predict the actions of individuals living in poverty, and understand what are often disappointing program outcomes. Recommendations suggest how psychology and behavioral decision making can impact policy research and design.